2020
DOI: 10.3389/fonc.2020.542957
|View full text |Cite
|
Sign up to set email alerts
|

CT Radiomics in Predicting EGFR Mutation in Non-small Cell Lung Cancer: A Single Institutional Study

Abstract: Objective: To evaluate the value of CT radiomics in predicting the epidermal growth factor receptor (EGFR) mutation of patients with non-small cell lung cancer (NSCLC), and combing with the clinical characteristic to construct the prediction model. Methods: Sixty-seven cases of NSCLC confirmed by pathology were enrolled. The pre-treatment chest CT enhanced images were used in Radiomics analysis. Two experienced radiologists delineated the region of interest (ROI) on open sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The s-CEA was suggested as a predictor to the EGFR mutation, 41,42 but pointed to have no predictive value in a recent work. 43 The age has been demonstrated to be predictive, 44 but also found to be ineffective for predicting the EGFR mutation. 43 To explore the potential clinical utility, an easy-to-use nomogram integrating the Combined Rad score and smoking was constructed and achieved the best prediction performance.…”
Section: Discussionmentioning
confidence: 99%
“…The s-CEA was suggested as a predictor to the EGFR mutation, 41,42 but pointed to have no predictive value in a recent work. 43 The age has been demonstrated to be predictive, 44 but also found to be ineffective for predicting the EGFR mutation. 43 To explore the potential clinical utility, an easy-to-use nomogram integrating the Combined Rad score and smoking was constructed and achieved the best prediction performance.…”
Section: Discussionmentioning
confidence: 99%
“…Before the process of feature selection, normalization of the extracted radiomics features to the range (0-1) was first performed. The Pearson's correction coefficient (PCC) analysis for reference to the previous studies, [24][25][26] and an optimal PCC value of 0.86 was applied to reduce the redundancy and maintain independent between the image features. The least absolute shrinkage and selection operator logistic regression (LASSO-LR) 27 algorithm was applied for further feature selection and construction of the MRIbased radiomics signature for pretreatment prediction of peripancreatic LN metastasis.…”
Section: Feature Selection and Radiomics Signature Developmentmentioning
confidence: 99%
“…At present, a number of studies have established a combined detection factor model to indicate EGFR gene mutation status for NSCLC patients by combining multiple predictors [ 99 ]. Wu et al [ 100 ] reported a study involving 67 NSCLC patients who were examined by enhanced chest CT before treatment and built the prediction models using clinical features and radiomics features. The AUC under the ROC of clinical characteristics and radionics characteristics was 0.8387 and 0.8815, respectively.…”
Section: Combined Prediction Modelsmentioning
confidence: 99%